PENDIDIKAN SUMATERA BARAT BERWAWASAN GENDER: LINTAS SEJARAH TAHUN 1890 – 1945 - Rosniati Hakim (Universitas Islam Negeri Imam Bonjol Padang, 2011)
Woman is the object and the target of educational audiences, which inevitably links with educational institutions as the embodiment of moral responsibility, as well as a necessity that can not be ignored. Education of women between 1890 to 1945, held under the Dutch government, and through a national movement, spawned a variety of organizations, to be realized in the form of schools, madrassas and other associations. Education at that time was shared between women and men, as are composed exclusively of women, as bequeathed by the past history of the hero women of West Sumatra.Keywords : Education and GenderCopyright © 2011 by Kafa`ah All right reservedDOI : 10.15548/jk.v1i2.79